Fracking, farmers, and rural electrification in India - T. Robert Fetter; Faraz Usmani (RWI - Leibniz-Institut für Wirtschaftsforschung, 2020)
The shale gas revolution in the United States induced an unprecedented commodity boom across northwestern India. Leveraging population-based discontinuities in the contemporaneous roll-out of India's national rural electrification scheme, we show that access to electricity increased total employment and nonagricultural employment in villages affected by this exogenous economic shock, but had no impact on labor markets elsewhere. This combination of two natural experiments highlights how complementary economic conditions drive heterogeneity in the labor-market impacts of rural electrification. It also helps explain the large variation in the reported impacts of such resource-intensive infrastructure investments globally. – – Die Schiefergasrevolution in den Vereinigten Staaten löste in Nordwestindien einen beispiellosen Rohstoffboom aus. Unter Ausnutzung bevölkerungsbezogener Diskontinuitäten bei der gleichzeitigen Einführung des nationalen ländlichen Elektrifizierungsprogramms Indiens zeigen wir, dass der Zugang zu Elektrizität die Gesamtbeschäftigung und die Beschäftigung außerhalb der Landwirtschaft in den Dörfern, die von diesem exogenen wirtschaftlichen Schock betroffen waren, erhöhte, aber keine Auswirkungen auf die Arbeitsmärkte anderswo hatte. Diese Kombination zweier natürlicher Experimente macht deutlich, wie komplementäre wirtschaftliche Bedingungen die Heterogenität der Auswirkungen der ländlichen Elektrifizierung auf den Arbeitsmarkt vorantreiben. Sie trägt auch dazu bei, die große Variationsbreite der berichteten Auswirkungen solcher ressourcenintensiver Infrastrukturinvestitionen weltweit zu erklären.
Keywords: H54; O13; O15; O18; Q40; Q56; R23; 330; rural electrification; heterogeneous impacts; labor markets; productive use; economic development; regression discontinuity; India